Evaluation of Radiation Doses Received by Organs at Risk in 3D Conformal and Intensity Modulated Radiotherapy for Head and Neck Cancer - Hassan, Hunar A.; Faraj, Kharman A.; Saeed, Zarean Y. (Sulaimani Journal for Pure and Applied Sciences, 2019)
The purpose of this study was to evaluate the doses delivered to the critical structures located close to the target volume during head and neck radiotherapy by 3D-CRT and IMRT technics in order to select possible treatment technic proper to head and neck regions. We have used all data collected from the Treatment Planning Systems (TPS) to conduct a pilot comparison between the two modalities. The comparison included the parameters of the target coverage, dose conformity and homogeneity for the planning target volume (PTV), the maximum and mean doses for organs at risk (OARs), the time required to deliver the prescribed dose, and number of Monitor Units (MU). The results showed that the dose conformity with IMRT plans for both PTV high and low risk was significantly better than those obtained with 3D-CRT plan. The dose uniformity in the PTV low risk was better with IMRT plan; mean homogeneity Index (HI) was 37.476 but for 3D-CRT were 43.465. IMRT technic achieved better PTV coverage. IMRT tended to provide a significant better OAR avoidance than 3D-CRT. We concluded that the 3D-CRT plan could not provide adequate OAR avoidance where many OARs are close to the PTVs. The IMRT plan, even though it takes longer time and more MUs, is the optimal plan for head and neck cancer treatment that derives to a better outcome while avoiding complication in the surrounded normal tissue.
Keywords: Intensity modulated radiotherapy; threedimensional conformal radiation therapy; head and neck cancer; radiation dose; organs at risk